2011
DOI: 10.1111/j.1542-4758.2011.00630.x
|View full text |Cite
|
Sign up to set email alerts
|

FGF‐23 is associated with cardiac troponin T and mortality in hemodialysis patients

Abstract: Fibroblast growth factor 23 (FGF-23) is elevated in patients with end-stage kidney disease and has been linked with mortality, vascular calcification, markers of bone turnover, and left ventricular hypertrophy. In this cohort study, we determined the correlates of FGF-23 (including cardiac troponin T [cTNT]) and determined its association with mortality over 3.5 years of follow-up in 103 prevalent hemodialysis patients. Mean age was 61.2 (15.5) and the mean dialysis vintage was 4.19 years (4.6). The median (in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 25 publications
2
10
0
Order By: Relevance
“…This accumulation of serum phosphate then elevates serum FGF23, which at high concentrations may promote cardiac dysfunction. This cycle appears to continue in CKD since increased ANP/BNP and FGF23 are predictive of CKD progression (10,45) and cardiac pathologies (15,21,22,26,35,43,52).…”
Section: Discussionmentioning
confidence: 99%
“…This accumulation of serum phosphate then elevates serum FGF23, which at high concentrations may promote cardiac dysfunction. This cycle appears to continue in CKD since increased ANP/BNP and FGF23 are predictive of CKD progression (10,45) and cardiac pathologies (15,21,22,26,35,43,52).…”
Section: Discussionmentioning
confidence: 99%
“…Because the small sample and short follow-up may decrease the study quality, we excluded 6 studies among which sample sizes were less than 200 and duration of followup was less than one year [6][7][8][9][10][11]. Nevertheless, the inclusion of these studies still did not materially alter the overall combined risk estimate.…”
mentioning
confidence: 94%
“…Kuro-o et al have shown mutated klotho gene to cause a syndrome resembling human ageing, including a short lifespan, infertility, arteriosclerosis, skin atrophy, osteoporosis and emphysema [16]. Holden et al ., studying patients with chronic kidney disease, have shown troponin T to be associated with FGF-23 [17]. In patients with chronic renal failure, serum FGF-23 concentrations were correlated with serum phosphate concentrations [18].…”
Section: Discussionmentioning
confidence: 99%